Household Coping and Response to Government Stimulus in an Economic Crisis : Evidence from Thailand - Khandker, Shahidur R.; Koolwal, Gayatri B.; Haughton, Jonathan; Jitsuchon, Somchai (World Bank, Washington, DC, 2014)
The crash of global financial markets in 2008 caused a ripple effect on economic demand and growth worldwide. Export-oriented economies were hit particularly hard, and many governments stepped in quickly with broad-ranging stimulus programs to lessen the effects on households of rising unemployment and falling income. To better understand the role that stimulus policy might play in softening the effects of these shocks, this paper examines recent nationally-representative data from Thailand, an export-dependent economy where a large-scale stimulus program was introduced in 2009. Using monthly data spanning 2006-2010, the paper uses sub-province-level community panel data to examine the effects of major components of the stimulus on household consumption, income, borrowing, and debt repaid. To address simultaneity of changes in government spending and household outcomes, the analysis estimates a dynamic panel regression, instrumenting the stimulus effect with second-order lagged outcome variables, and estimating the model using the Generalized Method of Moments. The results suggest that household participation in these programs helped smooth consumption. This increase in monthly consumption was not supported from household receipts from the government stimulus, but more likely through a reallocation of consumption and savings that included greater debt repayment. The paper typically finds stronger effects in urban compared with rural areas.